MEMBANGUN AKUNTANSI MANAJEMEN SYARIAH: MENDESAKKAH? - ., Sonhaji (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Abstract: Developing Syaria Management Acoounting: Is it Urgent? AccountingÂ Management was born from the root of Western capitalism characterized with egoistic, materialistic and individualistic values that potentially cause disfunctional behavior. Management Accounting is related more with behavioral aspect. This article seeks to identify the basic behavioral assumptions using an Islamic perspective. Islam worldview can be used to develop Sharia Management Accounting by using the rule: